Negative impact induced by foreign workers: evidence in Malaysian construction sector - Abdul-Rahman, H.; Wang, C.; Wood, Lincoln; Low, S. (Pergamon, 2012)
Though foreign workers served to overcome the labor shortage in the Malaysian construction market, over-dependence on foreign workers and the negative impacts induced have become a serious social problem. The aims of this research are to identify those negative impacts induced by foreign workers in the Malaysian construction market and to determine strategies in minimizing these negative impacts. Data were collected through a structured interview and survey. The questionnaires were delegated to professionals in construction projects who have direct contacts with foreign workers. Only respondents from those companies registered under the CIDB grade G7 were chosen for this survey. There were 117 sets of questionnaires completed and analyzed through the structured interviews. The three principal factors attracting foreign workers to the Malaysian construction market are “Preference of the employers”, “Lifestyle and working conditions”, and “Unattractiveness of the career pathway”. The main negative impacts induced by foreign workers are “Over-dependence on foreign workers”, “Increment in criminal activities or social problems”, and “Existence of illegal workers”. This research proposes that strategies such as “Attract local workers into the construction industry”, “Industrialized Building Systems”, “Eliminate illegal migration”, and “Improve governance structure” would be successful in minimizing negative impacts induced by foreign workers.